PENERAPAN PEMBELAJARAN AKTIF INOVATIF KREATIF EFEKTIF DAN MENYENANGKAN DENGAN MENGGUNAKAN PERMAINAN SUCKER BALL - Al Hamidi, Febriyan (Indonesian Journal of History Education, 2012)
This study aims to determine the results of classroom learning using the method of learning models PAIKEM Sucker ball game compared to the class using lecture methods vary. The study design used in this study is the type of experimental research. Based on research results, obtained an average post test experimental class is 75.47 and the average grade control was 67.97. For results of test calculations with an average difference of post-test scores obtained thitung = 1.403 while the ttabel = 1.35 for ? = 5% and dk = (32 +32-2) = 62 is obtained t (0.95) (62) = 1.35. Because thitung t (0.95) (74) so H0 is rejected, this means that there are significant differences in the quality of learning between the experimental and the control groups. Based on the research results can be concluded that there are differences in learning outcomes between the classes that use PAIKEM with learning outcomes using the lecture method